Ridership mismatch and spatial restructuring in the MyCiti bus rapid transit, city of Cape Town : the unintended outcome of land market forces? - Teessen, Minette (Stellenbosch : Stellenbosch University, 2023)
Teessen, M. 2023. Ridership mismatch and spatial restructuring in the MyCiti bus rapid transit, City of Cape Town: the unintended outcome of land market forces? Unpublished master thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/adf9627b-7055-4ec4-a698-9131e6ac8e7c